The effects of early mobilization in mechanically ventilated adult ICU patients: systematic review and meta-analysis - Wang, Lijie; Hua, Yusi; Wang, Luping; Zou, Xia; Zhang, Yan; Ou, Xiaofeng (Frontiers in Medicine, 2023)
Background: The effects of early mobilization (EM) on intensive care unit (ICU) patients remain unclear. A meta-analysis of randomized controlled trials was performed to evaluate its effect in mechanically ventilated adult ICU patients. Methods: Authors searched randomized controlled trials (RCTs) published in Medline, Embase, CENTRAL (from inception to November 2022). According to difference of timing and type, intervention group was defined as systematic EM group and comparator groups were divided into late mobilization group and standard EM group. The primary outcome was mortality. The secondary outcomes were ICU length of stay, duration of mechanical ventilation (MV) and adverse events. EM had no impact on 180-day mortality and hospital mortality between intervention groups and comparator groups(RR 1.09, 95% CI 0.89–1.33, p=0.39).  Systemic EM reduced the ICU length of stay (LOS) (MD -2.18, 95% CI -4.22– -0.13, p=0.04) and the duration of MV (MD -2.27, 95% CI -3.99– -0.56, p =0.009), but it may increase the incidence of adverse events in patients compared with standard EM group (RR 1.99, 95% CI 1.25–3.16, p=0.004). Conclusions: Systematic EM have no significant effects on short- or long-term mortality in mechanically ventilated adult ICU patients, but systematic EM could reduce the ICU LOS and duration of MV.